Surfing the brain. - Van de Ville, D.
In this paper, an overview with unification of techniques that deploy the wavelet transform in the spatial domain for the analysis of functional magnetic resonance imaging (fMRI) is presented.
Keywords: Brain; fMRI; Functional magnetic resonance imaging; Spatial domain; Wavelet transform